Divya-Herbal-Peya Decoction Harmonizes the Inflammatory Response in Lipopolysaccharide-Induced Zebrafish Model - Balkrishna A; Lochab S; Joshi M; Srivastava J; Varshney A (Dove Medical Press, 2021)
Acharya Balkrishna,1- 3 Savita Lochab,4 Monali Joshi,5 Jyotish Srivastava,5 Anurag Varshney1,2,6 1Drug Discovery and Development Division, Patanjali Research Institute, Haridwar, 249405, Uttarakhand, India; 2Department of Allied and Applied Sciences, University of Patanjali, Patanjali Yog Peeth, Haridwar, 249405, Uttarakhand, India; 3Patanjali Yog Peeth (UK) Trust, Glasgow, G41 1AU, UK; 4Department of Biology, Drug Discovery and Development Division, Patanjali Research Institute, Haridwar, 249405, Uttarakhand, India; 5Department of Chemistry, Drug Discovery and Development Division, Patanjali Research Institute, Haridwar, 249405, Uttarakhand, India; 6Special Centre for Systems Medicine, Jawaharlal Nehru University, New Delhi, IndiaCorrespondence: Anurag VarshneyDrug Discovery and Development Division, Patanjali Research Institute, NH-58, Haridwar, 249405, Uttarakhand, IndiaEmail anurag@prft.co.inBackground: Divya-Herbal-Peya (DHP) is a plant-based decoction containing fourteen herbs in precise quantities; usually prescribed by the practitioners in Ayurveda to alleviate stress and minimize the exasperating symptoms of recurring infections. Our study aims to provide an experimental validation to the immunomodulatory properties of DHP.Methods: Physico-chemical analysis of DHP was performed to evaluate the presence of secondary metabolites. The phytochemicals were then identified and quantitated through HPTLC, UHPLC, and GC-MS techniques. To address the scientific rationale behind DHP, lipopolysaccharide (LPS) was intraperitoneally injected in adult zebrafish to develop inflammatory response. Following LPS-induction, abnormality in locomotory behaviour was determined by evaluating the relative swim velocity and the rate of turning in experimental zebrafish. Pathophysiological effects were determined through opercular frequency, behavioural fever, and caudal fin damage. LPS-mediated inflammation was measured of pro-inflammatory cytokines, TNFα, IL-6, and IL-1β expression in the serum of study animals, by RT-PCR.Results: Our study phytochemically characterized and ascertained the presence of glycyrrhizin, rosmarinic acid, gingerol, cinnamic acid, protocatechuic acid, gallic acid, ellagic acid, piperine and cinnamaldehyde in DHP decoction. LPS induced aberrant locomotory patterns, behavioural fever and caudal fin damage in zebrafish. A significant increase in gene expression levels of pro-inflammatory cytokines, TNFα, IL-6, and IL-1β was also determined. However, these locomotory deviations and behavioural fever were negligible in zebrafish groups pre-administered either with DHP in a dose dependent manner or dexamethasone (DEX). The altered opercular rate, caudal fin damage and elevated transcription levels of pro-inflammatory genes upon LPS-induction were averted in groups pre-treated with DHP and DEX.Conclusion: DHP prophylactically prevented the LPS-induced abnormal behaviour and inflammation-related pathophysiology in zebrafish. Immunomodulatory properties of DHP may not have therapeutic intervention, but do confer nutraceutical health benefits against mild infections.Keywords: immunomodulatory, anti-inflammatory, zebrafish, phytometabolites, Divya-Herbal-Peya, herbal decoction